The principle of reason - Martin Heidegger (Indiana Univ. Press, 1991)
The book takes as its focal point Leibniz's principle: nothing is without reason. It shows here that the principle of reason is in fact a principle of being. It presents Heidegger's most extensive reflection on the notion of history and its essence. It also contains important discussions of language, translation, reason, objectivity, and technology as well as of such figures as Leibniz, Kant, and Aristote